2013
DOI: 10.1159/000350545
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Integrating Nephrologists into the Postoperative Cardiac Intensive Care Unit: A Cohort Study

Abstract: Background/Aims: We evaluated the potential preventive effect of Nephrology On-Site (i.e. nephrologists integrated into the postoperative cardiac intensive care unit, ICU, team) versus Nephrology On-Demand (i.e. nephrology consultation depending on intensivist criteria) in the ICU on in-hospital outcomes. Methods: This was a retrospective cohort study comparing outcomes during 2 consecutive time periods: from March 1, 2009 to February 28, 2010 with Nephrology On-Demand, and from March 1, 2010 to February 28, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Flores-Gama et al [15], in a retrospective cohort study, revealed the potential preventive effects of a nephrologist integrated into the postoperative cardiac ICU vs. nephrology consultation depending on intensivist's criteria in the ICU based on in-hospital outcomes. The results were favorable to a nephrologist 'part of the team', with a lower incidence of AKI, lower in-hospital mortality among patients with severe AKI and higher renal recovery rates.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Flores-Gama et al [15], in a retrospective cohort study, revealed the potential preventive effects of a nephrologist integrated into the postoperative cardiac ICU vs. nephrology consultation depending on intensivist's criteria in the ICU based on in-hospital outcomes. The results were favorable to a nephrologist 'part of the team', with a lower incidence of AKI, lower in-hospital mortality among patients with severe AKI and higher renal recovery rates.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The results were favorable to a nephrologist 'part of the team', with a lower incidence of AKI, lower in-hospital mortality among patients with severe AKI and higher renal recovery rates. Integrating nephrologists into the postoperative cardiac ICU team was associated with a lower incidence of AKI, and even patients who developed severe AKI had lower in-hospital mortality and higher renal recovery [15] . Table 1 presents the main statistics from the 6 papers described above.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The majority of the available studies reported recovery at hospital discharge [17,[19][20][21][22][23][24][25]. With the exception of studies focusing on long-term follow-up [4,5,10], recovery is mostly reported for all AKI patients (survivors and non-survivors) [15,16,18,19,[21][22][23]26]. Although inclusion of non-survivors is important from a pathophysiological point of view and essential for intervention trials, recovery of kidney function among survivors is probably more relevant from a patient's perspective and crucial for determining the burden of postdischarge nephrological follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…The available clinical trials either excluded patients with an unknown baseline Screat [9,19], used an imputed baseline Screat based on the Modification of Diet in Renal Disease (MDRD) equation (as suggested by ADQI and KDIGO) [4,16,17,23,25], used the minimum Screat measured during hospitalization [5,21], or did not mention how baseline Screat was determined [18,24]. The impact of using an imputed instead of the observed baseline on the incidence of AKI has been reported [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, how important is the cooperation of nephrologists and intensivists in the management of renal replacement therapy in the acute patient? [4]. How much weight on outcome can a cooperative approach like the one described in the Vicenza Model have?…”
mentioning
confidence: 99%